3D printing: enabling customer-centricity in the supply chain. (22nd March 2019) - Martinelli, Elisa Martina; Christopher, Martin
Three-dimensional printing (3DP) is used for multiple purposes in many fields and it is attracting attention, both academically and managerially, in the context of a customer-centric approach to supply chain management. The purpose of this paper is to explore how 3DP enables supply chain customer-centricity through value co-creation by the analysis of a case study, the manufacture of an innovative 3D printed component in the aerospace sector. The research highlights that: 1) the usage of 3DP enables the adoption of an external customer-centric supply chain orientation drawing on four sources of value co-creation; 2) value co-creation network based on 3DP requires a particular form of collaboration and coordination, bringing specific benefits for all the partners involved. A conceptual framework, leading to propositions, is developed identifying the elements of a customer-centric supply chain based on the principles of co-creation. Finally, theoretical and managerial implications and future research directions are outlined.